Enhancing Customer Relationship Management with Data Analytics: Insights from Retail Survey - Jabado, Roula; Jallouli, Rim (Journal of Telecommunications and the Digital Economy, 2024)
In the contemporary digital era, understanding the role of Data Analytics Capabilities (DAC) in Customer Relationship Management (CRM) systems is essential for effective marketing decisions. DAC refers to the skills and knowledge in using technological tools, techniques, and methodologies to extract meaningful and actionable insights from various data sources. The originality of the study lies in providing an external perspective from customers on the benefits of effective DAC to improve the performance of CRM systems in the retail industry. Specifically, it evaluates the roles of technological CRM system quality, employee interaction-management capabilities empowered with the CRM system, and the DAC outcomes in enhancing the overall customer satisfaction for both online and in-store experiences. The methodology employs a quantitative approach that includes a survey for data collection of 380 retail customers, an exploratory factor analysis and a multi-linear regression analysis. Theoretically, findings advance our understanding of retail CRM systems by providing empirical evidence quantifying the positive impact of DAC outcomes on customer satisfaction. Practically, results offer managerial insights for leveraging technology and human capabilities to enhance in-store and online customer relationships. Acknowledging geographical and industry limitations, future research could explore the research model across various contexts.